Answer:
The standard equation of the parabola is:
![y=(x^2)/(6)+x+3](https://img.qammunity.org/2023/formulas/mathematics/high-school/3bxzstpa3h1igaj58wyoosxoerzk6zlxzl.png)
Step-by-step explanation:
The focus of the parabola, (h, f) = (-3, 3)
The directrix: y = 0
The equation of a parabola is of the form:
![y=(1)/(4(f-k))(x-h)^2+k](https://img.qammunity.org/2023/formulas/mathematics/college/unuvxaznisilrudin3ykgfcf7eylgy3159.png)
The distance from the focus to the vertex is equal to the distance from the vertex to the directrix
f - k = k - y
3 - k = k - 0
k + k = 3 + 0
2k = 3
k = 3/2
Substitute k = 3/2, f = 3, and h = -3 into the equation above
![\begin{gathered} y=(1)/(4(3-(3)/(2)))(x-(-3))^2+(3)/(2) \\ y=(1)/(4((3)/(2)))(x+3)^2+(3)/(2) \\ y=(1)/(6)(x+3)^2+(3)/(2) \\ y=((x+3)^2)/(6)+(3)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/pkk5v64retlwqvmqnthkvwmev7bb9lhb8y.png)
This can be further simplified as:
![\begin{gathered} y=(x^2+6x+9)/(6)+(3)/(2) \\ y=(x^2+6x+9+9)/(6) \\ y=(x^2+6x+18)/(6) \\ y=(x^2)/(6)+(6x)/(6)+(18)/(6) \\ y=(x^2)/(6)+x+3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/9lj2hedu20058r9i9gjqpuh2csrpkfr9vb.png)
Therefore, the standard equation of the parabola is:
![y=(x^2)/(6)+x+3](https://img.qammunity.org/2023/formulas/mathematics/high-school/3bxzstpa3h1igaj58wyoosxoerzk6zlxzl.png)